Study on the electromagnetic fields of a novel small-angle transducer used in high-precision inertial sensors. Issue 5 (12th August 2019) - Chen, Zongyu; Dong, Jiuzhi; Li, Xingfei
Abstract : Purpose: Microsyn signal generators have been used in high-precision inertial sensors for their good structural stiffness and high sensitivity. However, as the stator and the rotor of the microsyn are both constructed of silicon-steel laminations with high permeability, an extremely small non-concentricity between the stator and rotor of microsyn will cause two random reaction torques acting on the output axis. As a result, difficulty arises in compensating for these random reaction torques. This study aims to investigate the electromagnetic fields of a novel angular transducer characterized by high sensitivity. Design/methodology/approach: Based on the operation principles of the new transducer, the output voltage is decided by the time rate of change of the net magnetic flux of each output pole. The transient analysis of the electromagnetic field of the transducer is carried out by ANSYS Maxwell-3D. Findings: The distributions of the magnetic flux of the transducer's interior and eddy current on the rotor are consistent with the results of theory analysis. Moreover, the leakage flux mainly distributes nearby the excitation poles. The novel small-angle transducer also possesses a remarkably low reaction torque and power loss. Practical implications: Study on the electromagnetic fields of the new transducer not only provides a powerful basis to further improve the precision of the new transducer but also expands the scope of applications of the new transducer. Originality/value: This new transducer is not only characterized by a high sensitivity, high linearity and fast response but also extremely low reaction torque and power losses. Thus, the new transducer is suitable for high-precision inertial sensors.